Factors that influence customer loyalty in the short term insurance industry in South Africa - Parbhoo, Nikesh Harish (My University, 2012)
Customer loyalty is a key driver of customer retention, retaining market share, increasing profitability and decreasing both customer acquisition and customer retention costs in any business. The South African short term insurance players face many challenges such as increased competition from non-traditional insurers, increased customer sophistication, and a move away from the traditional broker model of selling. Customer retention has become more difficult than ever. This study fills the gap in the research with regards to the drivers of customer loyalty, specifically within the short term insurance industry in South Africa. This study identifies the loyalty measure types that describe customer loyalty, and the various customer clusters that exemplify the identified loyalty factors. It also establishes whether customer rewards programs have any influence on customer loyalty. A quantitative research approach was followed. A questionnaire using a 7-point Likert scale was developed and piloted. The final questionnaire was administered on a sample set of 194 respondents, based mainly in Johannesburg. The results were subject to an exploratory factor analysis to determine the loyalty factors, a cluster analysis to determine the relevant customer clusters, and a T-test to determine if loyalty reward programs have any influence on the identified loyalty factors. 3 customer loyalty factors emerged: price, brand loyalty and brand promotion. Furthermore, four customer cluster types emerged: the brand savvy cluster that is very brand aware; the price sensitive cluster that will defect on premium increases; the ‘problem childs’ cluster that has a high propensity to complain and not defect; and the loyal cluster that is the most price insensitive but also will not easily brand switch nor will they bad-mouth their insurance company. Another key insight has been that loyalty reward programs do not have any influence on the 3 loyalty factors. Recommendations are provided to executives and management to improve customer loyalty
MBA thesis - WBS
Keywords: Consumer loyalty; Insurance, Short-term; Short-term insurance; Customer loyalty